PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA PELAYANAN PERAWAT DI RUMAH SAKIT MILIK PEMERINTAH - Darmayani, Dina; Pramagistra Nurshabrina, Latesia; Veranita, Mira (JURNAL PENDIDIKAN, HUMANIORA, LINGUISTIK DAN SOSIAL (JAGADDHITA), 2024)
The enactment of Law No. 11 of 2020 on Job Creation (Omnibus Law) has intensified competition within the hospital sector. Government-owned hospitals face increasing competition from private hospitals that possess more flexible and abundant resources. Additionally, the implementation of the National Health Insurance (JKN) has resulted in a continual rise in BPJS patient visits. However, delayed BPJS Health claim reimbursements have caused severe liquidity crises in government hospitals, where BPJS patients constitute 80-95% of total hospital admissions. This financial uncertainty, specifically regarding income and work compensation, has led to diminished work motivation, increased stress levels, and heightened internal conflict among staff members, ultimately hindering human resource development programs under already high workloads. This study aims to analyze the effect of compensation and work motivation on nurses' service performance in government hospitals. A quantitative descriptive-analytic design was employed using a cross-sectional approach. Data were collected through structured interviews and questionnaires, and analyzed using content analysis by comparing findings from two prior research studies. The results demonstrate that the independent variables—compensation (X1) and work motivation (X2)—significantly influence nurses' service performance (Y) in government hospitals.